Working conditions and job satisfaction: A study of domestic helpers with Filipino and non-Filipino employers - Ching, Johanna Paula Y. (Animo Repository, 2004)
This study describes the profiles, working conditions, and levels of job satisfaction of selected domestic helpers employed in upper class Filipino and non-Filipino households. Twenty domestic helpers were interviewed, 10 from each type of household. The results indicate that majority of domestic helpers are migrants from provinces in Luzon, Visayas and Mindanao. Most of the helpers are single women between the ages of 17 and 59, and have some secondary education. Domestic helpers experience mostly favourable working conditions in both Filipino and non-Filipino households. Those employed by the latter receive higher wages, whereas the Filipino-employed helpers have significantly better benefits. Both household types mainly require logn working hours but with moderate workload since basic agreed tasks are shared by several helpers. Some aspects of working conditions vary according to nationality of household members. Majority of helpers interviewed are generally highly satisfied and none are completely dissatistied. Relationship with employers, followed by nature of tasks are the factors most attributed to high job satisfaction. Helpers employed by non-Filipino families are generally more satisfied with the various components of working conditions than are Filipino-employed helpers.